Expression of lymphocyte activation markers of preterm neonates is associated with perinatal complications - Sava, Florentina (BMC Immunol, 2016)
BACKGROUND: Inappropriate activation of T lymphocytes plays an important role in perinatal complications. However, data on T lymphocyte activation markers of preterm infants is scarce. We investigated the association between gender, gestational and postnatal age, preeclampsia (PE), premature rupture of membranes (PROM) as well as prenatal steroid treatment (PS) and the frequency of activated T lymphocyte subsets (HLA-DR+, CD69+, CD25+, CD62L+) and major T lymphocyte subpopulations (CD4, CD8, Th1, Th2, naïve, memory) in peripheral blood during the first postnatal week in preterm infants. RESULTS: Cord blood and peripheral blood samples were collected from 43 preterm infants on the 1st, 3rd, and 7th days of life. We assessed the frequency of the above T lymphocyte subsets using flow cytometry. The ‘mixed effect model’ was used to analyze the effects of clinical parameters on T lymphocyte markers. The frequency of CD25+ T lymphocytes was higher in PROM. The frequency of CD4+ and CD8+ cells and the CD4+/CD8+ cell ratio was decreased in PE. The frequency of CD62L+ T lymphocytes was higher in male compared with female infants. PS did not affect the frequency of the investigated markers. CD4+ CD25+ cells had a lower frequency at birth than on day 7. Th2 lymphocytes had a lower frequency on postnatal days 1 and 3 when compared to day 7. CONCLUSIONS: Our observations indicate that alterations affecting the expression of T lymphocyte activation markers are associated with the above factors and may play a role in the development of perinatal complications.